In vitro culture and structural differences in the major immunoreactive protein gp36 of geographically distant Ehrlichia canis isolates - (:unkn) unknown (My University, 2014)
Contribution: Study design, molecular and phylogenetic analysis and drafting of the manuscript
Keywords: African Research